Teacher's Physical Activity and Mental Health During Lockdown Due to the COVID-2019 Pandemic - Aperribai, Leire; Cortabarria, Lorea; Aguirre, Triana; Verche, Emilio; Borges, África (Frontiers in Psychology, 2020)
The Covid-19 pandemic has led teachers to an unpredictable scenario where the lockdown situation has accelerated the shift from traditional to online educational methods, and relationships have been altered by the avoidance of direct contact with the others, with implications for their mental health. Physical activity seemed to be a factor that could prevent from mental disorders such as anxiety or depression in this peculiar situation. Therefore, the aims of this study were to explore how teachers have been affected by the lockdown in respect to their mental health and their relationships in three main fields, work, family and social relationships; and to know which is the role of physical activity in the mentioned variables. For that purpose, an online survey was designed to collect quantitative and qualitative data. Results showed that indoor physical activity acts as preventive in lockdown situations, while the level of activity does not affect mental health. Also, teachers have experienced higher levels of depression and distress due to the workload generated during the lockdown. In conclusion, to prevent health problems among teachers in future similar situations it would be important to facilitate the practice of physical activity at home. Furthermore, teacher training in blended or online educational methods would be crucial for their favorable work development.